2022
DOI: 10.1021/acscatal.2c01952
|View full text |Cite
|
Sign up to set email alerts
|

High-Ionic-Strength Wastewater Treatment via Catalytic Wet Oxidation over a MnCeOx Catalyst

Abstract: Catalytic wastewater treatment has rarely been applied to treat high-ionic-strength wastewater (HISWW) as it contains large amounts of catalyst poisons (e.g., Cl – ). This work investigates the catalytic wet oxidation (CWO) of phenol over a MnCeO x catalyst in the presence of high NaCl concentrations where the combination of MnCeO x and NaCl promoted the CWO of phenol. Specifically, in the presence of NaCl at a concentration of 200 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The ionic strength of influent domestic wastewater is typically between 0.003 to 0.10 M (ref. 12 and 18) while the ionic strength of digestor recycle streams can be as high as 0.17 M. 18 Many municipal wastewater treatment plants also receive significant industrial discharges, which can have ionic strength levels that exceed 1 M. [36][37][38] Since ionic strength can impact the surface properties of Bacillus spores, future studies may investigate the effects of the higher ionic strength conditions (e.g. >1 M) present when a large volumetric fraction of the influent is received from industrial sources.…”
Section: Implications For Ba Ames and Future Considerationsmentioning
confidence: 99%
“…The ionic strength of influent domestic wastewater is typically between 0.003 to 0.10 M (ref. 12 and 18) while the ionic strength of digestor recycle streams can be as high as 0.17 M. 18 Many municipal wastewater treatment plants also receive significant industrial discharges, which can have ionic strength levels that exceed 1 M. [36][37][38] Since ionic strength can impact the surface properties of Bacillus spores, future studies may investigate the effects of the higher ionic strength conditions (e.g. >1 M) present when a large volumetric fraction of the influent is received from industrial sources.…”
Section: Implications For Ba Ames and Future Considerationsmentioning
confidence: 99%
“…The maximum conversion was found to be 85% at 1.0 g/L catalyst loading and 200 g/L concentration of NaCl for the 24 h reaction duration. 29 It was observed that phenol oxidation increases with an increase in NaCl concentration since NaCl reduces the carbon deposition on the surface of the catalyst and promotes the oxidation of hydrocarbons and reoxidation of the catalyst. Besides, the salt water system facilitated the regeneration of the used catalyst via a salt water wash under reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The CWO of phenol was investigated by using a Mn/CeO x catalyst in the presence of NaCl. The maximum conversion was found to be 85% at 1.0 g/L catalyst loading and 200 g/L concentration of NaCl for the 24 h reaction duration . It was observed that phenol oxidation increases with an increase in NaCl concentration since NaCl reduces the carbon deposition on the surface of the catalyst and promotes the oxidation of hydrocarbons and reoxidation of the catalyst.…”
Section: Introductionmentioning
confidence: 99%